STUDI IDENTIFIKASI KEBERADAAN Escherichia coli PADA ES BATU YANG DIGUNAKAN OLEH PEDAGANG WARUNG MAKAN DI TEMBALANG - Rainy Rifta; Budiyono Budiyono; Yusniar Hanani Darundiati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Ice cubes are food products that already known by the public. However, ice can be a food product that carried pathogenic microorganisms such as Escherichia coli, if not handled properly. The existence of Escherichia coli in ice was estimated to occur during the production, distribution, including processing time where the hygiene practices of vendors worker or merchant involved. The purpose of this study was to identify the existence of Escherichia coli in ice cubes that were used by food vendors at Tembalang. This was the study identification with cross sectional approach type of research. 46 samples chosen by simple random sampling. The data were collected using questionnaires and laboratory tests and then analyzed using frequency distribution and cross table. The results showed that 100% of the samples containing coliform bacteria that were not eligible under the Regulation of the Minister of Health No. 492/Menkes/Per/IV/2010 (0 APM/100 ml). The results of the Escherichia coli existence identification showed that 23 (50.0%) ice cube samples positively contain Escherichia coli. The results were divided into two: 13 (56.5%) samples were factory-made and 10 (43.5%) samples were home-made. From the interviews, there were 40 (87.0%) food vendor’s merchant that still didn’t do the hygiene practice well. It could be concluded that the microbiological quality of ice cubes used by food vendors at Tembalang is not that good. Therefore, the food vendor should improve hygiene practices, especially in maintaining the cleanliness of the ice cube container to ensure the safety of products ice cubes are safe for consumption by the consumer.